THE SPEED OF SOUND WAVE PROPAGATION IN AIR USING THE STANDING WAVE METHOD AND THE MECHANIKAL PROPERTIES OF SOUND - Nazokat Turaevna Kadirova (Journals Park Publishing, 2026)
This article discusses the nature of sound as a physical phenomenon. Sound is shown to be a wave-like motion that arises as a result of periodic deformation of particles in an elastic medium. Sound is generated and propagated only in elastic media. When the vibration frequency of the medium’s particles falls within the human audible range, sound can be perceived. In theoretical calculations, the vibrations of particles in the medium through which sound propagates are usually considered as harmonic oscillatory motion. Sound is a mechanical wave produced by a vibrating body. For example, when a tuning fork or human vocal cords vibrate, the surrounding air molecules begin to oscillate in accordance with the motion of the source. These oscillations are transmitted successively to neighboring molecules and, upon reaching the ear, cause vibrations of the eardrum. This process results in the generation of nerve impulses perceived by the brain.
Keywords: Tuning fork, vibration, infrasound, ultrasound, frequency, intensity, impact, amplitude, timbre, harmonic oscillation, acoustics.